2016
DOI: 10.1007/s12571-016-0567-9
|View full text |Cite
|
Sign up to set email alerts
|

Low permeability triple-layer plastic bags prevent losses of maize caused by insects in rural on-farm stores

Abstract: Participatory on-farm trials were conducted to assess effectiveness of Purdue Improved Crop Storage (PICS™) bags for storage of maize in small-scale farmers' stores in rural villages in eastern Kenya. A PICS bag is a three-layered hermetic bag-system that forms a barrier against the influx of oxygen and the escape of carbon dioxide. Jute, woven polypropylene or PICS bags were filled with shelled maize grain, purchased from the participating farmers, and the three sets of bags kept in the farmers' own stores fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…Results of the present study show that rodents are the second most important maize storage pest problems in Kenya, after insects. The Larger grain borer and the Maize weevil (Sitophilus zeamais) are the main storage insect pest in farm storage in Kenya (Bett and Nguyo 2007;De Groote et al 2013;Ng'ang'a et al 2016). This observation is supported by the results of the regression model which showed that the presence of rodents in storage contributed significantly to total postharvest losses incurred.…”
Section: Magnitudes Of Lossesmentioning
confidence: 86%
“…Results of the present study show that rodents are the second most important maize storage pest problems in Kenya, after insects. The Larger grain borer and the Maize weevil (Sitophilus zeamais) are the main storage insect pest in farm storage in Kenya (Bett and Nguyo 2007;De Groote et al 2013;Ng'ang'a et al 2016). This observation is supported by the results of the regression model which showed that the presence of rodents in storage contributed significantly to total postharvest losses incurred.…”
Section: Magnitudes Of Lossesmentioning
confidence: 86%
“…Better practices and technologies can reduce storage losses by almost 98% of those seen with traditional methods [70], irrespective of length of storage period. For example, Purdue improved crop storage (PICS) has been shown to reduce grain damage in terms of weight loss due to insects from over 40% to under 1% [83]. Unsanitary and unhygienic handling [22] during storage and transportation further adds to these losses.…”
Section: Transport and Storage Stagementioning
confidence: 99%
“…Hermetic storage structures, including metal silos and portable hermetic bags have been successfully tested under laboratory conditions against diverse pests, including S. zeamais, P. truncatus and S. cerealella (García-Lara et al, 2013a,b;Tefera et al, 2011). Consequently, these structures were tested at field-scale in vulnerable regions, with successful results (Gitonga et al, 2013;Ng'ang'a et al, 2016). In Kenya, the usage of metal silos and super grain bags lead to reduction of losses caused by S. zeamais and P. truncatus to less than 5% (De Groote et al, 2013).…”
Section: Strategies For Reduction Of Postharvest Food-grain Lossesmentioning
confidence: 99%